2015
DOI: 10.1051/0004-6361/201525778
|View full text |Cite
|
Sign up to set email alerts
|

The jet and the disk of the HH 212 low-mass protostar imaged by ALMA: SO and SO2emission

Abstract: Context. The investigation of the disk formation and jet launching mechanism in protostars is crucial to understanding the earliest stages of star and planet formation. Aims. We aim to constrain the physical and dynamical properties of the molecular jet and disk of the HH 212 protostellar system at unprecedented angular scales, exploiting the capabilities of the Atacama Large Millimeter Array (ALMA). Methods. The ALMA observations of HH 212 in emission lines from sulfur-bearing molecules, SO 9 8 −8 7 , SO 10 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 47 publications
10
96
0
Order By: Relevance
“…outflows (Lavalley-Fouquet et al 2000;Podio et al 2015). As shown by our simulations, this shape modeling (in the narrow jet limit) allows one to estimate the sideways ejection velocity from the IWS and the length scale of the bowshock.…”
Section: Discussionsupporting
confidence: 60%
“…outflows (Lavalley-Fouquet et al 2000;Podio et al 2015). As shown by our simulations, this shape modeling (in the narrow jet limit) allows one to estimate the sideways ejection velocity from the IWS and the length scale of the bowshock.…”
Section: Discussionsupporting
confidence: 60%
“…The recent images from the Atacama Large Millimeter/submillimeter Array (ALMA) of a potentially planet-forming disk around a young star with an age of only 0.5-1 Myr, HL Tau, (ALMA Partnership et al 2015) has highlighted the importance of the physics and chemistry of the early protostellar stages: how do stars evolve during their earliest evolutionary stages and in particular, to what degree does the chemistry reflect this early evolution relative to, e.g., the conditions in the environment from which the stars are forming? Already during its first years ALMA has demonstrated enormous potential for addressing these issues with its high angular resolution and sensitivity making it possible to zoom in on solar system scales of young stars and map the chemical complexity in their environments (e.g., Pineda et al 2012;Jørgensen et al 2012Jørgensen et al , 2013Persson et al 2013;Codella et al 2014;Sakai et al 2014;Friesen et al 2014;Lindberg et al 2014;Oya et al 2014;Murillo et al 2015;Podio et al 2015;Belloche et al 2016;Müller et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Keplerian disks have been observed around protostars in the early evolutionary stages, such as Class I (Hogerheijde 2001;Brinch et al 2007;Lommen et al 2008;Jørgensen et al 2009;Lee 2010;Yen et al 2013Yen et al , 2014Harsono et al 2014), Class 0/I (Tobin et al 2012;Hara et al 2013)and Class 0 (Choi et al 2010;Codella et al 2014;Lee et al 2014;Ohashi et al 2014;Tobin et al 2015) protostars,butthe formation process is not yet well understood. Recent Atacama Large Millimeter Array (ALMA) observations have suggested that some molecular species are enhanced at the boundary between the infalling envelope and the forming Keplerian disk, suggesting thermal desorption from the grain surfaces (Sakai et al 2014a(Sakai et al , 2014bPodio et al 2015;Oya et al 2016). Thermal desorption of the grain-surface species is one of the astrophysical processes that affects the chemical evolution of a nebula.…”
Section: Introductionmentioning
confidence: 99%